EDUCATIONAL POTENTIALS FROM THE APPLICATION OF RUSSIAN WRITERS' EPISTOLARY HERITAGE INTO RUSSIAN LANGUAGE AND LITERATURE CLASSES (Journal of Foreign Language Studies, 2019)
The use of Russian writers' epistolary heritage in Russian literature lesson allows the full achievement of its educational objectives. Also, the epistolary heritage can be successfully used in the organization of the extracurricular activities in the Russian literature classes. The article presents ways of intergrating letters into literature lessons and recommends the use of Russian writers' epistolary heritage at school. Examples of introduction of the letters fragments in the lesson plan are also provided with an analysis of the efficiency of using the epistolary Russian writers' heritage in class and in extracurricular activities.
Keywords: epistolary heritage; letters of Russian writers; the use of letters in the classroom; educational objectives of the lesson; training objectives of the lesson; ways to include letters in the lesson